In-Hospital Outcome of Early Versus Late Coronary Intervention in Patients Undergoing Thrombolysis after Acute Myocardial Infarction - Tariq, Muhammad Naeem; Samore, Naseer Ahmed; Rashid, Muhammad Humayoun; Nadeem, Asif; Saif, Mohsin; Jokhio, Abdul Rehman; Azad, Naseem; Noeman, Ahmad; Yamin Bukhar, Syeda Neelam; Chaudhry, Azhar Ali (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the In-hospital outcome of early versus late coronary intervention in patients undergoing thrombolysis after acute myocardial infarction (STEMI). Study Design: Analytical Cross sectional study. Place and Duration of Study: Department of Cardiology, Punjab Institute of Cardiology, Lahore Pakistan from Jul 2021 to Dec2021. Methodology: Total of (n=100) patients regardless of gender between 30-80 years of age, presented with acute ST-elevated myocardial infarction (STEMI) at emergency room of PIC, Lahore and undergo thrombolysis with a thrombolytic agent after taking the informed consents were selected by a consecutive sampling technique. The demographic information which includes (name, age, gender, H/O diabetes, duration of STEMI) was noted. Then patients were randomly divided in two groups (Group A & B). In Group-A, patients were undergone PCI within 24 hours of thrombolysis. In Group-B, patients were undergone PCI after 24 hours of thrombolysis. Then all patients were followed-up in coronary care units for 07 days. If reinfarction occurs or patient was died during hospital stay, it was recorded. All the information was noted in a preformed structured proforma. Results: Out of 100 patients, 10 % (n=10) were in age group of 30-45 years and 90 % (n=90) were in age group of 46-80 years. The mean age was calculated as 60.16 ± 7.13 years. There were 90 (90 %) males whereas 10 (10 %) were females. The frequency of Re-Infarction in early Intervention group was 2(2%) and in late Intervention group it was 10%. (p<0.05).The frequency of mortality in early Intervention group was 2 (02%) and in late Intervention group it was 10%. (p< 0.05). Conclusion: Frequency of re-infarction as well as mortality was comparatively low in Intervention group. Therefore, the immediate restoring the patency of occluded coronary arteries can prevent or decrease myocardial damage due to acute myocardial infarction and henceforth, decrease morbidity and mortality..